The Politeness Strategies of Criticizing Utterance by The Students of English Department of Muhammadiyah University of Surakarta - Handayani, Kinanthi Wahyu, Dra. Siti Zuhriah Ariatmi, M.Hum (2017)
This research is aimed at describing (1) criticism strategy of criticizing utterances and (2) politeness strategy of criticizing utterance. The data used in this research are utterances used by the students of the first semester of English department of Muhammadiyah University of Surakarta. The technique of collecting data is DCT model. The techniques of analyzing data are reduction, analysis and conclusion. The data are analyzed by using criticism strategy of Nguyen and politeness strategy of Brown and Levinson. Based on the data analysis, the researcher found that: (1) there are eleven criticism strategies used by students, namely: request of change takes 31%, negative evaluation 8%, identification of problem 5%, advice of change 3%, asking/presupposing 3%, demand of change 3%, suggestion of change 3%, consequences takes 2%, disapproval takes 1%, other hint takes 1%, statement of difficulties takes 1% and 34% utterances are not belonging to any criticism strategy. There are 32% utterances of the students used appropriate criticism strategy and 68% utterances of the students used inappropriate criticism strategy because the students fail to choose appropriate strategy in relation with power property, distance of the hearer and the seriousness of the case that makes them are over polite and impolite, (2) there are five politeness strategies used by the students namely: bald on record strategy takes 36%, positive politeness strategy takes 14%, negative politeness strategy takes 11%, combination strategies takes 6%, bald off record strategy takes 2% and 31% utterances are not belong to any politeness strategy. There are 27% utterances of the students used appropriate politeness strategy and 73% utterances used inappropriate politeness strategy because the students fail to choose appropriate strategy in relation with the power property of the speaker, the distance among the speaker and the hearer, and the seriousness of the case that makes them are over polite and impolite.